Smart City: Opportunities and Challenges in Public Services and Its Relation to The Protection of Rights and Privacy in Big-Data Era - Kukuh Tejomurti; Padma Widyantari (Hang Tuah Law Journal, 2018)
This article investigates Smart City program with the utilization of internet technology that government assumes as means to solve problems every city encounters, such as traffic jam, retribution, public security, and trash dumping. To provide public service, Smart City collects and manages personal data information of citizens from the intended city and puts it into a Big Data base. This program with Big Data technology has been successful addressing problems in cities. On the other hand, a consequence on how to protect public’s electronic-based personal data should be taken into account as well. Collecting, Processing, and Saving Information of public personal data may carry on particular risk, including violation on individual’s rights and privacy, when it is not well managed and set under a very clear policy, especially when its big data server is outside the territory of Indonesia. In general conclusion, the government needs to enact a regulation in constitutional and national level and/or regional regulation which specifically sets on how to prevent the misuse of electronicbased personal data and what law that regulates any violation against individual rights and privacy, as well as a regulation called privacy by design.